Double-Coated Poly(butyl Cyanoacrylate) Nanoparticles as a Potential Carrier for Overcoming P-Gp- and BCRP-Mediated Multidrug Resistance in Cancer Cells - Kaushal, Neeraj; Chen, Zhe-Sheng; Lin, Senshang (Frontiers in Nanotechnology, 2021)
The present study evaluates poly(butyl cyanoacrylate) nanoparticles (PBCA-NPs), double-coated with Tween 80 and polyethylene glycol (PEG) 20000 as a potential carrier system for overcoming P-glycoprotein (P-gp) and breast cancer resistant protein (BCRP)-mediated multidrug resistance (MDR) in cancer cell lines. Doxorubicin-loaded PBCA-NPs were prepared by the anionic polymerization method and were successively double-coated with Tween 80 and PEG 20000 at varied concentrations. MDR reversing potential was investigated by cellular uptake in P-gp overexpressing cell line. And, the outcomes were verified by modified MTT assay in P-gp or BCRP overexpressing cell lines. The findings from the cell uptake study indicate that double-coated PBCA-NPs significantly enhanced doxorubicin accumulation within the cells. MTT assays revealed that double-coated PBCA-NPs significantly potentiated the sensitivity of doxorubicin in P-gp overexpressing cells, in comparison to free doxorubicin, single-, and un-coated PBCA-NPs, respectively. Moreover, further increase in concentration with Tween 80, double-coated PBCA-NPs significantly enhanced the sensitivity of doxorubicin in BCRP overexpressing cell line, in comparison to single- and double-coated formulations (with lower concentration of Tween 80). Hence, it could be concluded that double-coated PBCA-NPs can be used as a potential carrier for enhancing doxorubicin accumulation in MDR cancer cells.